Improving The Educational Process in Higher Educational Institutions with The Help of Modern Pedagogical Technologies (European Journal of Pedagogical Initiatives and Educational Practices, 2023)
Modern education requires solving various problems and problems of our time, first of all, the problems of socialization and adaptation of students. What our graduates will be depends on the whole system of organization of the educational process. Now the result of teaching a child at school has been determined - the formation of key competencies. It is impossible and irrational to form them using only traditional methods.